Fabrikarne from the golden nuggets - Bautista, Honesto M.; Lim, Luis T.; Salas, Patrocinio (Quezon City College of Engineering, 1970)
Capacity: 2,566,200 lbs/yr -- Land area: one hectare -- Total fixed capital investment: 502,274 -- Operating cost at maximum production: 635,417 -- Annual sales at maximum production: 641,550 -- Pay off time: 8.7 years -- Break-even point: 95.40% -- Shutdown point: 45.00%
Typescript.
Submitted in partial fulfillment of the requirements in ChE 62.
Keywords: Factories -- Design and construction; Extraction (Chemistry).; Soy oil